A solution for global hygienic challenges regarding the application of heater-cooler systems in cardiac surgery. (January 2023) - Foltan, Maik; Nikisch, André; Dembianny, Jan; Miano, Anna-Lena; Heinze, Johannes; Klar, Dennis; Göbölös, Laszlo; Lehle, Karla; Schmid, Christof
71.759 surgical procedures were performed in 2019 with the aid of cardiopulmonary bypass in Germany. To adjust the patient's body temperature on extracorporeal circulation, the application of a heater-cooler unit (HCU) is mandatory. However, in case of insufficient sanitisation of HCU, life-threatening infections can be transmitted by the device to the patients, including Legionella bacteria, Mycobacterium chimaera, Pseudomonas aeruginosa. To avoid disease transmission, as a requirement for safe medical practice established by regulatory authorities, HCUs must be regularly disinfected by hazardous chemicals posing a danger for both handling humans and the environment. Therefore, to comply with regulations, HCU manufacturers have introduced both timely and financially extensive sanitisation procedures. Our paper describes a novel, effective and easy to handle disinfection method for the above problematics without utilising hazardous chemicals. The method's technical principle is electrolysis, resulting in drinking water quality regarding the analysed germs in the worldwide most commonly utilised heater-cooler device. The main aim of the study was to prove the efficacy and reliability of the device cleansing process. Furthermore, the economic impact of the novel method was evaluated. Therefore, we have undertaken 60 microbiological sampling series between December 2019 and November 2020 from a conventional HCU (3T LivaNova, Germany). During the total investigational period, no contamination with Pseudomonas aeruginosa or Legionellae could have been demonstrated in the HCU. The extreme slow-growing nontuberculous M. chimaera was detected only in one sample obtained from diamond electrode cleansed HCU water, and source of contamination was promptly eliminated by a simple technical modification of the device test-site. Additionally, the diamond electrode application is beneficial for eliminating potentially hazardous cleansing material from the process, which may affect otherwise both patients operated on cardiopulmonary bypass and the perfusionists.